2017
DOI: 10.1097/mpg.0000000000001530
|View full text |Cite
|
Sign up to set email alerts
|

Second‐line Agents in Pediatric Patients With Autoimmune Hepatitis

Abstract: Cyclosporine had the highest response rate at 6 months in children with standard-treatment-refractory AIH; however, it also had the highest rate of adverse events. MMF was the second most efficacious option with a low adverse effect rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 66 publications
0
36
0
3
Order By: Relevance
“…Treatment failure occurs in 7%-9% of adults and is associated with increased risk of progression to cirrhosis and liver failure, with mortality rates as high as 30%. (403) Second-line therapies for treatment failure include MMF, (404)(405)(406)(407)(408)(409)(410) calcineurin inhibitors (CsA (411)(412)(413)(414)(415)(416) , TAC (417)(418)(419)(420) ), mercaptopurine (421,422) and biologics (rituximab, (423) infliximab (424) ).…”
Section: Second-line Treatmentsmentioning
confidence: 99%
“…Treatment failure occurs in 7%-9% of adults and is associated with increased risk of progression to cirrhosis and liver failure, with mortality rates as high as 30%. (403) Second-line therapies for treatment failure include MMF, (404)(405)(406)(407)(408)(409)(410) calcineurin inhibitors (CsA (411)(412)(413)(414)(415)(416) , TAC (417)(418)(419)(420) ), mercaptopurine (421,422) and biologics (rituximab, (423) infliximab (424) ).…”
Section: Second-line Treatmentsmentioning
confidence: 99%
“…A recent meta-analysis by Zizzo et al found that 64% of children treated for refractory AIH had at least 1 adverse event. 5 In our study, we show successful azathioprine monotherapy in a small group of children with asymptomatic AIH, however, in those treated with azathioprine monotherapy, liver enzymes do not normalize as quickly as those children treated with prednisone. There is no data regarding the relative risk of up to 3 months of steroid therapy compared with several months of mildly increased liver enzymes (below  2 the upper limit of normal), however, adverse effects of even short courses of steroid treatment are well known.…”
Section: Replymentioning
confidence: 46%
“…Although studies specifically designed to evaluate MMF safety in paediatric neurology are not available, our patients and other children treated with MMF both in neurological 18 and in other paediatric conditions 5,6,39 seem to support a favourable safety profile. In recent studies on adult NMOSD, MMF had significantly better tolerability than azathioprine.…”
Section: Safetymentioning
confidence: 76%
“…2 MMF is also largely used as a steroid-sparing agent for chronic immunosuppression in rheumatology and in neurological autoimmune and immune-mediated conditions, with data suggesting a relatively safe profile. [3][4][5][6] MMF has been used for nearly two decades in myasthenia gravis, 7,8 although its role is less clear in chronic inflammatory demyelinating polyradiculoneuropathy. 9 In central nervous system (CNS) autoimmune and immune-mediated conditions, MMF has been increasingly used in relapsing demyelinating diseases such as neuromyelitis optica spectrum disorders (NMOSD) 4,10-14 and myelin oligodendrocyte glycoprotein (MOG)-associated disease.…”
mentioning
confidence: 99%